Risk assessment of desertification using GIS in upper and lower reaches of Mond basin, Iran - Masoud Masoudi; Parviz Jokar (Acta Universitatis Carolinae Geographica, 2018)
The present paper attempts to develop a new model by considering various indicators of different types of land degradation or desertification. These types include water erosion, soil salinity, vegetation degradation, and lowering of ground water table. The indicators can be used to find areas with higher rates of degradation which are called Potential Risk Areas (risky zones) in this paper, and can also be used to estimate the probability that degradation will increase in these areas. The Mond river basin, located in the southern part of Iran, has been selected as a test area to assess the risk and kind of desertification. For this purpose two sub basins of the Khormuj and Khane-Zenian & Siakh-Darengun have been chosen for detailed study as these two provide enough variation in climatic conditions like rainfall and topography. The different kinds of data gathered from records and published reports of the different governmental offices of Iran have been used for this purpose. The thresholds for the severity classes of indicators have been established and then the hazard map for each indicator of types of desertification has been prepared in a GIS. The risk maps of water erosion, soil salinization, lowering of water table, and vegetation degradation have been produced for both sub basins. Areas on the maps are assigned to risk classes on the basis of risk scores derived by considering the cumulative effects of all indicators overlying the area in the GIS. It was possible to distinguish the areas under ‘actual risk’ from areas under ‘potential risk’ of desertification types. Also areas under potential risk are classified to subclasses with different probability level to show a statistical picture of risk in future. The final map of risk of desertification is produced by overlaying all four maps of degradation types. Between the two basins the overall environmental condition in the Khormuj sub basin is worse. Results show that potential risk areas are much widespread than areas under actual risk in the upper reaches (of both sub basins) of Mond basin, indicating further threat of land degradation or desertification in the future. The percent of areas under actual risk are much more extensive in the lower reaches (Khormuj sub basin), indicating the higher degradation at present. It is hoped that this attempt using GIS will be found applicable for other regions of the world.